2019
DOI: 10.1007/s10198-019-01031-8
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic long-term care expenditure: associated socio-demographic and economic factors

Abstract: Objective An increasing number of persons across the world require long-term care (LTC). In Spain, access to LTC involves individuals incurring out-of-pocket (OOP) expenditure. There is a large body of literature on the incidence of catastrophic OOP payments in access and participation in health systems, but not in the field of LTC nor the determinants of these expenses. Our aim was to analyse the socio-demographic and economic factors associated with different levels of catastrophic LTC expenditure in the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…36 Other studies from developed countries also reported a higher risk of CHE among the lowest income households than the highest income ones. 37 , 38 Unlike in our findings, the provinces located in northern, northeastern, and central parts of Iran were reported to have better access to healthcare services. 39 The reasons for this difference require further investigation.…”
Section: Discussioncontrasting
confidence: 99%
“…36 Other studies from developed countries also reported a higher risk of CHE among the lowest income households than the highest income ones. 37 , 38 Unlike in our findings, the provinces located in northern, northeastern, and central parts of Iran were reported to have better access to healthcare services. 39 The reasons for this difference require further investigation.…”
Section: Discussioncontrasting
confidence: 99%
“…view than the earlier literature. Some study found that households living in a rural area, and female participants were highly prone to nancial risk due to higher out-of-pocket health payments [14,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Excessively high out-of-pocket medical payment can lead to catastrophic expenditure [4,21,22]. Even for countries with tax-based universal health insurance systems, we do not have sufficient evidence to show the impact of economic recession on health care payments [23][24][25][26][27].…”
Section: Literature Reviewmentioning
confidence: 99%